Mass spectrometry imaging (MSI) of Santa Barbara Basin sediment core SPR0901-05BC - Susanne Alfken (PANGAEA, 2018)
Ultra-high resolution records for UK extquotesingle37, the C29 stanol/stenol ratio and the thaumarchaeal lipid based CCaT from the uppermost ~5 cm sediment section of the Santa Barbara Basin box core (SPR0901-05BC) are presented. Single spot data for the analyzed sediment surfaces are presented as a 2D-matrix before and after correction of tilted layers, and as a downcore profile obtained after averaging individual horizons. Data are intended as an outlook into the use of mass spectrometry imaging in multiproxy studies. Congruent elemental mapping for Ca/Ti and Si/Ti obtained by microXRF is presented as a 2D matrix.